Semantiska vågor i undervisningen: Likheter och skillnader i skolämnena matematik och samhällskunskap - Jakobsson, Martin; van Bommel, Jorryt; Randahl, Ann-Christin; Modig, Niclas (Utbildning & Lärande, 2023)
If students are to build knowledge, it is important to connect disciplinary knowledge to students’ everyday knowledge when teaching. In this study, the relationship between disciplinary- and everyday knowledge in subject-teaching is analysed, based on the semantic dimensions used in Legitimation Code Theory. Un-packing disciplinary concepts through concrete examples implies a shift towards a context-dependent everyday knowledge, while re-packing them entails a shift towards disciplinary abstractions and context-independent generalizations. Over time these shifts constitute so-called semantic waves argued to facilitate students´ knowledge building. Earlier research suggest that the form of these semantic waves can differ between school-subjects. Therefore, this article examines semantic waves in two contrasting subjects – Mathematics and Social Science Education, aiming at a better understanding of how and why semantic waves differ. The results reveal that the forms of semantic waves differ between the two subjects. In Mathematics, when teaching different geometrical concepts, the semantic shifts through un-packing and re-packing were frequent and evenly distributed. When teaching about pricing and household in Social Science, un-packing activities dominated, making shifts biased towards everyday knowledge. These differences are discussed in terms of semantic waves constituting a different pulse when making knowledge-building possible in Mathematics and Social Science.